Relationship between knowledge level and reproductive health behavior among adolescent girls: A cross-sectional study - Berta Afriani; Oca Mawadah (Lentera Perawat, 2026)
Background: Adolescent reproductive health is an important aspect of adolescent girls' development because it relates to their ability to understand bodily changes, maintain reproductive hygiene, and make responsible health decisions. Adequate knowledge is needed to prevent risky behavior, reproductive tract infections, and misinformation commonly obtained from peers and digital media. Objective: This study aimed to analyze the relationship between knowledge level and reproductive health behavior among adolescent girls at SMA Sentosa Bhakti OKU. Methods: This study used an analytical quantitative design with a cross-sectional approach. The population consisted of all 30 female grade XII students at SMA Sentosa Bhakti OKU, and the sample was selected using total sampling. The independent variable was reproductive health knowledge, while the dependent variable was reproductive health behavior. Data were collected using questionnaires and analyzed using univariate and bivariate analyses. The bivariate analysis used the Chi-square test with an expected-count assessment; if the assumption was not met, the Fisher-Freeman-Halton Exact Test was used as an alternative. Results: Most respondents had a high level of knowledge (13 respondents; 43.3%), followed by moderate knowledge (7 respondents; 23.3%) and low knowledge (10 respondents; 33.3%). Reproductive health behavior was mostly categorized as good (12 respondents; 40.0%), sufficient (8 respondents; 26.7%), and poor (10 respondents; 33.3%). The analysis showed a significant relationship between knowledge level and reproductive health behavior among adolescent girls (p = 0.003). Conclusion: Knowledge level was significantly associated with reproductive health behavior among adolescent girls. Schools, school health units, and community health centers should strengthen structured, adolescent-friendly, and sustainable reproductive health education.